Advancing Renewable Energy Materials: Corrosion and Strength Optimization of 17-4 PH Stainless Steel for Geothermal Turbines - Muhammad Alvito Faros; Riri Murniati; Agus Hadi Santosa Wargadipura (CV. Aksara Global Akademia, 2025)
This research explores the engineering and performance evaluation of 17-4 PH stainless steel as a potential material for turbine blades in geothermal power plants (PLTP). To promote renewable energy innovation in industrial engineering, this study focuses on improving material reliability through microstructural optimization and mechanical property control. The material was produced using the investment casting method at PT SPVMB and then subjected to four heat treatment variations: H900, H1025, AVG (average), and as-cast conditions, with reference to ASTM A747 standards. Mechanical and corrosion characterization were performed through hardness and tensile tests, electrochemical corrosion analysis using geothermal water from the Dieng PLTP, and microstructural observation using an optical microscope. The results showed that the H900 condition had the highest hardness and yield strength (48.46 HRC and 939.25 MPa), but its corrosion rate was relatively high. In contrast, the H1025 heat treatment provides balanced mechanical strength (43.88 HRC and 860.91 MPa) with the lowest corrosion rate (0.027 mm/year), supported by a uniform tempered martensite structure. These findings indicate that heat treatment optimization significantly improves the suitability of 17-4 PH stainless steel for sustainable geothermal applications. The H1025 condition meets all the requirements for geothermal turbine blades, including hardness, strength, and corrosion resistance, potentially extending component life and reducing maintenance costs. Furthermore, the results of this study strengthen the agenda for developing durable, environmentally friendly materials to support renewable energy systems. This study also provides practical insights for industry in selecting the optimal heat treatment that combines mechanical performance and corrosion resistance in extreme geothermal environments.